The reliability of students' ratings of the teaching efficiency of college instructors in a Philippine teacher-education institution - Cruz, Amelita V. (Antonio) 1935- (s.n.], 1968)
This study investigated the reliability of students' ratings of teachers' classroom efficiency as measured by the Purdue Rating Scale for Instructors. Results show that the students' ratings as measured by the Purdue Rating Scale for College Instructors in a Philippine Teacher-Education institution are reliable, and therefore, valid.